2011
DOI: 10.1158/1541-7786.mcr-10-0467
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Fatty Acid Synthase Induces Ubiquitination and Degradation of Phosphoinositide-3-Kinase Signaling Proteins in Ovarian Cancer

Abstract: Aberrations within the phosphoinositide-3-kinase (PI3K) pathway occur in greater than 45% of ovarian carcinomas. The PI3K cascade transmits signals from ErbB receptors downstream to S6 and 4EBP1, which are involved in protein biosynthesis. Many ovarian carcinomas reveal hyperactivation of ErbB1 (epidermal growth factor receptor) or ErbB2 (HER2/neu). Unfortunately, the benefit of anti-ErbB drugs is yet rather limited in ovarian carcinomas. Thus, novel targeting strategies are needed for ovarian carcinomas. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 34 publications
8
62
0
1
Order By: Relevance
“…A study by Tomek et al (34) indicated that the inhibition of FASN induces ubiquitination and degradation of PI3K signaling proteins in ovarian cancer. A previous study demonstrated that small interfering RNA silencing of FASN decreased the PI3K/Akt/NF-κB signaling pathway in vitro (32); however, the mechanism (s) responsible for the inhibition of Akt activity due to the downregula tion of FASN have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tomek et al (34) indicated that the inhibition of FASN induces ubiquitination and degradation of PI3K signaling proteins in ovarian cancer. A previous study demonstrated that small interfering RNA silencing of FASN decreased the PI3K/Akt/NF-κB signaling pathway in vitro (32); however, the mechanism (s) responsible for the inhibition of Akt activity due to the downregula tion of FASN have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase (FASN) promotes proliferation and EMT via transcriptional regulation of E-cadherin and Ncadherin and its overexpression correlates with dissemination and peritoneal metastasis of ovarian cancer (136). In this context, it was shown that blockage of FASN induces ubiquitination and degradation of PI3K signaling proteins in ovarian cancer (137). The involvement of FASN in the generation of phospholipids involved in the formation of membrane microdomains that accommodate receptor tyrosine kinases, including HER1 and HER2, has also been demonstrated (138).…”
Section: Fatty Acid Synthase (Fasn) and Fatty-acid Binding Protein 4 mentioning
confidence: 99%
“…For example, blocking proteasome function may activate autophagy. [476][477][478][479] Thus, when using inhibitors it is critical to know whether the inhibitors being used alter autophagy in the particular cell type and context being examined. In addition, because 3-MA could have some autophagy-independent effects in particular settings it is advisable to verify that the 3-MA-sensitive degradation is also sensitive to general lysosomal inhibitors (such as NH 4 Cl or leupeptin).…”
mentioning
confidence: 99%